1967
DOI: 10.1042/bj1030258
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the aflatoxins B1, G1, and G2 on protein and nucleic acid synthesis in rat liver

Abstract: A comparison has been made of the difference spectra obtained by causing various aflatoxins (B(1), G(1) and G(2)) to interact with calf-thymus DNA. The effect of these toxins on RNA and protein synthesis by rat-liver slices has been measured. The extent of their inhibitory action on the synthetic reactions was proportional to the degree of spectral shift obtained with their interaction with DNA. It is proposed that their toxicity depends on this interaction. It was demonstrated that the RNA polymerase of nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

1968
1968
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(10 citation statements)
references
References 15 publications
0
9
1
Order By: Relevance
“…Thus, inhibition of RNA synthesis is accompanied by nucleolar segregation (Svoboda and Higginson, 1968), and inhibition of protein synthesis by the detachment of ribosomes from the rough-surfaced endoplasmic reticulum and the proliferation of smooth membranes (Butler, 1966;Clifford, Rees and Stevens, 1967;Svoboda and Higginson, 1968;Harley, Rees and Cohen, 1969). Apparent membrane degranulation is often seen as a response to drug challenge and accompanies the induction of enzymes associated with nascent smooth membrane and is also associated with drug detoxication (Arcos, Conney and Buu-Hoi, 1961;Orrenius and Ericsson, 1966;Conney, 1967).…”
mentioning
confidence: 99%
“…Thus, inhibition of RNA synthesis is accompanied by nucleolar segregation (Svoboda and Higginson, 1968), and inhibition of protein synthesis by the detachment of ribosomes from the rough-surfaced endoplasmic reticulum and the proliferation of smooth membranes (Butler, 1966;Clifford, Rees and Stevens, 1967;Svoboda and Higginson, 1968;Harley, Rees and Cohen, 1969). Apparent membrane degranulation is often seen as a response to drug challenge and accompanies the induction of enzymes associated with nascent smooth membrane and is also associated with drug detoxication (Arcos, Conney and Buu-Hoi, 1961;Orrenius and Ericsson, 1966;Conney, 1967).…”
mentioning
confidence: 99%
“…Experiments pertaining to the role of aflatoxin as a cytotoxin were done on biological systems. The mode of action of aflatoxin in the molecular level was largely revealed by the work of Clifford and Rees (1967). They studied the effect of AFB 1 on DNA replication, transcription of messenger RNA or translation of m-RNA into protein.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level aflatoxins impart their effect either interfering with DNA replication or transcription of messenger RNA into protein. Clifford and Rees (1967) revealed that the administration of a single dose of aflatoxin (7 mg/kg body weight) resulted in slow development of periportal necrosis. Hepatic enzymes were released into the serum after 48 h of poisoning.…”
Section: Structure and Function Of Aflatoxin Moleculesmentioning
confidence: 98%